Baltes' SOC model of successful ageing as a potential framework for stroke rehabilitation. (March 2014) - Donnellan, C.; O'Neill, D.
Abstract Aim: The aim of this paper is to explore approaches used to address some stroke rehabilitation interventions and to examine the potential use of one of the life-span theories called the Baltes' model of selective optimisation with compensation (SOC) as a potential framework. Key findings and implications: Some of the key considerations for a stroke rehabilitation intervention framework are highlighted including accommodating for the life management changes post stroke, alterations in self-regulation, acknowledge losses and focusing on a person-centred approach for transition from acute rehabilitation to the home or community setting. The Baltes' SOC model is then described in terms of these considerations for a stroke rehabilitation intervention framework. Conclusions and recommendations: The Baltes' SOC model may offer further insights, including ageing considerations, for stroke rehabilitation approaches and interventions. It has potential to facilitate some of the necessary complexities of adjustment required in stroke rehabilitation. However, further development in terms of empirical support is required for using the model as a framework to structure stroke rehabilitation intervention. Implications for Rehabilitation There is a scarcity of theoretical frameworks that can facilitate and be inclusive for all the necessary complexities of adjustment, required in stroke rehabilitation. In addition to motor recovery post stroke, rehabilitation intervention frameworks should be goal orientated; address self-regulatory processes; be person-centred and use a common language for goal planning, setting and attainment. The Baltes' SOC model is one such framework that may address some of the considerations for stroke rehabilitation, including motor recovery and other life management aspects.